Pie in the sky. Series 1 [videorecording (DVD)] - Griffiths, Richard, 1947-2013; Sinclair, Malcolm, 1950-; Steed, Maggie (Acorn Media : Freemantle Media Enterprises, 2000)
"After 25 years in the force, Detective Inspector Henry Crabbe has lost his appetite for the job. He plans to take early retirement and open his dream restaurant, Pie in the Sky. But his accountant wife, Margaret, doesn't think the numbers add up. And his boss, ACC Fisher needs him around to handle those delicate cases at which he excels. Although craving retirement, Crabbe discovers that crime solving can be just as hard to resist as his signature steak and kidney pie."--Container